POLLUTING ACTIVITY: THE EVIL OF THE 21ST CENTURY - Diniz, Maria Helena; Santiago, Mariana Ribeiro (Revista Direitos Sociais e Políticas Públicas (UNIFAFIBE), 2025)
This article analyzes the theme of pollution and its connection with the preservation of human life and the ideal of sustainable development. The choice of the theme is justified in view of the serious threat that polluting agents currently represent for humanity, flora, and fauna. The aim of this study is to highlight the role of the State, companies, and individuals in spreading the theme of sustainability and in the effectiveness of preserving the environment. Therefore, pollution as ecological damage is specifically studied. After that, the principles that guarantee the environment are highlighted. Then, the relationship between sustainability and environmental awareness is analyzed. Finally, the need for a solidary society to preserve the environment is emphasized. The research observes the bibliographic and documentary procedures. In the approach, the legal dialectical method is used. In conclusion, it is understood that there is a link between strengthening solidarity and controlling pollution.